2015
DOI: 10.21061/jots.v41i1.a.6
|View full text |Cite
|
Sign up to set email alerts
|

<p>The “Who, What, and How Conversation”: Characteristics and Responsibilities of Current In-service Technology and Engineering Educators</p>

Abstract: and add 15.6 million jobs to the 2012 employment level of 145.4 million. Of the 818 occupations for which the Bureau of Labor Statistics (BLS) produces and publishes projections data, 667 are projected to add jobs and 151 are expected to decline in employment during the 2012-2022 period. Some of the fastest projected growth will occur in the healthcare, healthcare support, construction, and personal care fields. Together, these four occupational groups are expected to account for more than 5.3 million new jobs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
5
8
0
Order By: Relevance
“…About half of the participants reported taking a higher education course that discussed methods for teaching interdisciplinary STEM concepts (e.g., science and engineering). The demographic and preparation data from this research and the full study (Love & Wells, 2017) were consistent with studies examining T&E educators at a national level (Love, 2015;Ernst & Williams, 2015). …”
supporting
confidence: 73%
See 2 more Smart Citations
“…About half of the participants reported taking a higher education course that discussed methods for teaching interdisciplinary STEM concepts (e.g., science and engineering). The demographic and preparation data from this research and the full study (Love & Wells, 2017) were consistent with studies examining T&E educators at a national level (Love, 2015;Ernst & Williams, 2015). …”
supporting
confidence: 73%
“…Additionally, the sample of observed teachers consisted of primarily White males, which presents a limitation considering the diversity in the actual population of T&E educators. However, it is noteworthy that the convenience sample used in this study is actually reflective of national T&E educator characteristics (Love, 2015;Ernst & Williams, 2015). Accounting for recognized limitations, the modified RTOP provided a viable instrument for quantifying teacher levels of science and T&E PCK, which is discussed in the following section.…”
Section: Training and Interrater Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative certification paths for new technology and engineering education teachers have been recognized as a way to alleviate teacher shortages, with teachers licensed through means other than through a traditional universitybased teacher preparation program (Hoepfl, 2001). In a nationwide comprehensive review of teachers using the Schools and Staffing Survey (SASS) administered by the U.S. Department of Education, Ernst and Williams (2015) found that technology and engineering education teachers are more likely to receive certification through an alternative certification program than other teachers (21.6% vs. 14.5%).…”
Section: Alternative Certification Meeting Shortages?mentioning
confidence: 99%
“…Workforce Development teachers can and often carry higher caseloads of students with IDEA disabilities that have individualized education plans (IEPs) and students with LEP than core academic teachers. In some situations, Workforce Development teachers can actually have higher caseloads of IEP students than special education teachers (Ernst & Williams, 2015;Williams, Kaui, & Ernst, 2015). Avramidis, Bayliss, and Burden (2000) found that teachers who had better teacher training exhibited better and positive attitudes toward inclusion of special education students in their classroom and felt more confident to meet those students' needs.…”
Section: Introductionmentioning
confidence: 99%